6‐3: Distinguished Paper: Highly Efficient Fluorescent Blue Materials and Their Applications for Top Emission OLEDs. Issue 1 (30th May 2018) - Masuda, Tetsuya; Nakano, Yuki; Takahashi, Yoshiaki; Ito, Hirokatsu; Okinaka, Keiji; Kambe, Emiko; Kawamura, Yuichiro; Kuma, Hitoshi
Abstract : We developed new fluorescent blue dopants (BDs) for achieving high efficient blue organic light emitting diode (OLED). The new BD showed both high photoluminescent quantum yield >0.9 and highly horizontal orientation (S'>0.9) in the doped film with keeping a chemical stability by introducing suitable substituents. We developed hole transporting materials and optimized the combination of hole transporting layers to decrease a carrier accumulation at the interface between electron blocking layer/emission layer (EML). We found that the external quantum efficiency dependency from low to high current density was turned flat by promoting hole injection into EML. The Top Emission OLED using the new BD and the optimized device architecture exhibited high efficiency of L/J/CIEy around 200 at CIEy=0.043.